2021
DOI: 10.1155/2021/6151973
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Screening Combined with Target Gene Panel Testing Increased Etiological Diagnostic Yield in Deaf Children

Abstract: Genetic testing is the gold standard for exploring the etiology of congenital hearing loss. Here, we enrolled 137 Chinese patients with congenital hearing loss to describe the molecular epidemiology by using 127 gene panel testing or 159 variant testing. Sixty-three deaf children received 127 gene panel testing, while seventy-four patients received 159 variant testing. By use of 127 gene panel testing, more mutant genes and variants were identified. The most frequent mutant genes were GJB2, SLC26A4, MYO15A, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In this study, we performed exome sequencing analysis for 351 affected individuals with hearing loss. Among the identified causal genes, variants in GJB2 and SLC26A4 were most frequently identified in this cohort, which is similar to previous reports ( Fu et al, 2019 ; Xie et al, 2021 ). Here, we reported the identification of four novel variants in the CDH23 gene ( Table 1 ), which significantly expanded the mutation spectrum of CDH23 -associated non-syndromic autosomal recessive deafness.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we performed exome sequencing analysis for 351 affected individuals with hearing loss. Among the identified causal genes, variants in GJB2 and SLC26A4 were most frequently identified in this cohort, which is similar to previous reports ( Fu et al, 2019 ; Xie et al, 2021 ). Here, we reported the identification of four novel variants in the CDH23 gene ( Table 1 ), which significantly expanded the mutation spectrum of CDH23 -associated non-syndromic autosomal recessive deafness.…”
Section: Discussionsupporting
confidence: 91%
“…Exome sequencing presented an advantage in the early diagnosis of hearing loss 12 , 18 , 40 , 41 and of other genetic disorders. 42 , 43 , 44 , 45 , 46 However, the high cost and long turnaround time limit the applicability of newborn genetic screening.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previous studies have shown that approximately 25% of cases of hearing loss are missed by existing newborn hearing screening (NBHS) programs, wherein two-thirds receive a diagnosis of severe to profound hearing loss later. 11 , 12 Previous studies have indicated that hearing loss among newborns in the NICU was associated not only with clinical risk factors, such as cytomegalovirus infection, craniofacial malformation, family history of hearing loss, duration of NICU stay, oxygen exposure, or low birth weight, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 but also with genetic disorders, which have been shown with the wider use of genetic testing to be associated with hearing loss. 21 Microarray or limited genomic sequencing were used in screening for underlying hearing loss in the general neonatal population because of its low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In European countries, many people are affected; they possess a pathogenic variation in GJB2 gene coding region with several deletions. Deletion can either be in a homozygous state or heterozygous and impairs transcriptional level gene expression by excluding regulatory factors preceding the GJB2 gene [48,49].…”
Section: Approved Galley Proofmentioning
confidence: 99%